CLINICAL TERMINOLOGY . WORD-FORMATION GREEK , SUFFIXES AND PREFIXES (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article offers an overview of the system of word formation in clinical terminology .Medical terms have been drawn from many languages. A large majority from Greek and Latin. The main part of this article consists of examples containing the most common roots, prefixes and suffixes will clarify the whole field.It will be found that the long and formidable sounding medical terms are a combination of words, which describes parts of body, a function or a combination